EXPRESSION OF MULTIDRUG RESISTANCE-RELATED PROTEIN (MRP-1), LUNG RESISTANCE-RELATED PROTEIN (LRP) AND TOPOISOMERASE-II (TOPO-II) IN WILMS' TUMOR: IMMUNOHISTOCHEMICAL STUDY USING TMA METHODOLOGY - Fridman, Eduard; Skarda, Jozef; Pinthus, Jonatan H; Ramon, Jonathan; Mor, Yoran (Biomedical papers, 2008)
Aims: MRP-1, LRP and TOPO-II are all associated with protection of the cells from the adverse effects of various chemotherapeutics. The aim of this study was to measure the expression of these proteins in Wilms' tumor (WT).Materials and Methods: TMA block was constructed from 14 samples of WT's and from xenografts derived from them. Sections of the TMA were used for immunostaining against MRP-1, LRP and TOPO-IIa.Results: All normal kidneys expressed MRP-1 but were either weakly or negatively stained for LRP and TOPO-IIa. In WT samples, MRP-1 was universally expressed, exclusively in the tubular component, while there was no expression of LRP and TOPO-IIa showed heterogeneous distribution. The xenografts varied in their MRP-1 and TOPO-IIa expression and exhibited weak/negative staining of LRP.Conclusions: This study shows that although all the proteins evaluated, had different expression patterns in the tumor samples, the most prominent changes in expression were found for MRP-1. The exact clinical implications of these changes in expression and their relevance to the resistance of these tumors to chemotherapy requires further investigation. The finding of different expression profiles for the multidrug resistance proteins in the original WT's and their xenografts suggests that the results of animal cancer models may be difficult to interpret.
Keywords: MRP (multidrug resistance related protein)/LRP (lung resistance protein)/TOPO-II (topoisomerase II)/Nephroblastoma/